Analisis Pengaruh Kebijakan Dividen dan Struktur Modal terhadap Tax Avoidance : Studi Empiris pada Perusahaan Sektor Consumer Non Cyclicals di Bursa Efek Indonesia Tahun 2019-2023 - Hermansyah, Erlan; Afridayani, Afridayani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study addresses the critical issue of tax avoidance among companies, focusing on how Dividend Policy and Capital Structure influence this behavior within non-cyclical consumer sector firms listed on the Indonesia Stock Exchange from 2019 to 2023. Understanding these financial strategies is vital, as tax avoidance can significantly impact government revenue and corporate governance. Employing a quantitative approach with secondary data and purposive sampling, 135 samples were analyzed using panel data regression in E-Views 12. The results reveal that while Dividend Policy does not significantly affect tax avoidance, Capital Structure plays a notable role in shaping tax avoidance strategies. This finding suggests that firms with specific financing mixes may exploit debt levels to minimize taxable income, highlighting the importance of financial leverage in tax planning. The insignificant influence of Dividend Policy may imply that payout decisions are less directly linked to tax avoidance motives within this sector. These insights contribute to a better understanding of corporate financial behavior and provide implications for regulators aiming to curb aggressive tax avoidance practices by monitoring capital structures. Policymakers and investors should consider the impact of leverage on tax compliance when designing oversight frameworks and investment strategies. This research underscores the nuanced relationship between financial policies and tax behavior, emphasizing the need for tailored regulatory measures to promote transparency and fairness in corporate taxation.